La aritmética modular y algunas de sus aplicaciones (2011)
En este trabajo se hace una revisión de los aspectos históricos, disciplinares, algunas aplicaciones y elementos pedagógicos de la aritmética modular. / Abstract. The Modular Arithmetic was introduced by Gauss in "Disquisitiones Arithmeticae" in 1801, in Modular Arithmetic are structure sets of congruences provided with two operations, induced from the usual Arithmetic in the integers. Some of its applications: chryzodes, calendars, criptography and determination of prime numbers can be studied in the classroom as encouraging tools.